2014
DOI: 10.1089/jmf.2013.0087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preservation Methods of Oil Palm Sap (Elaeis guineensis) on the Reproductive Indices of Male Wistar Rats

Abstract: Thirty male Wistar rats, split into five groups of six rats each, were administered different forms of oil palm tree (Elaeis guineensis) sap samples by gavage based on 1.5% of their weekly body weights. Group 1 which served as control received only water, group 2 received pasteurized palm sap (PPS), group 3 received market palm wine (MPW), group 4 received frozen palm sap (FPS), whereas group 5 received fresh palm sap (FrPS). Chemical composition of the sap samples was determined. Normal feed and water were fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
1
2
0
2
Order By: Relevance
“…On-going work by the authors had observed that a blend of activated charcoal and aged palm wine (ACAPS) increased egg-laying performance, ovarian weight development and decreased weight loss due to egg-laying in treated hens compared to the control. Similar observations of improved fertility and litter size were also reported in Wistar rats fed freshly-tapped palm wine 126 . Smallholder pig farmers in Cambodia found the feeding of pigs with Borassus flabellifer palm sap improved body weight in pigs and was of more economic benefits to the farmers compared to its use in sugarproduction 68,69 .…”
Section: Alcoholssupporting
confidence: 86%
“…On-going work by the authors had observed that a blend of activated charcoal and aged palm wine (ACAPS) increased egg-laying performance, ovarian weight development and decreased weight loss due to egg-laying in treated hens compared to the control. Similar observations of improved fertility and litter size were also reported in Wistar rats fed freshly-tapped palm wine 126 . Smallholder pig farmers in Cambodia found the feeding of pigs with Borassus flabellifer palm sap improved body weight in pigs and was of more economic benefits to the farmers compared to its use in sugarproduction 68,69 .…”
Section: Alcoholssupporting
confidence: 86%
“…They use Elaesis guineensis sap, the unfermented colorless exudate from tapped unopened spathe of the oil palm tree (Elaeis guineensis, Jacq) to induce and maintain lactation following parturition. The Elaeis guineensis sap is a traditional drink usually consumed as a nourishing beverage in some tropical countries (17,18). This freshly collected sap has 7.2 of neutral pH and a very low content of ethanol i.e., 0.09%.…”
Section: Introductionmentioning
confidence: 99%
“…The fermented palm sap, called palm wine is the commonest form of the beverage. Before, the consumption of the beverage (palm sap/wine) was a common feature in virtually all ceremonies (traditional festivals, weddings and funerals) where it was served as an indication of hospitality [2]. Nowadays, the drink is becoming more and more present in the diet as it is supplied daily in restaurant or sold in the street.…”
Section: Introductionmentioning
confidence: 99%